ANGKA PARTISIPASI SEKOLAH (APS) PADA MASYARAKAT PESISIR DAN PERAN ORANG TUA DALAM PENDIDIKAN ANAK DI KECAMATAN SEMARANG UTARA KOTA SEMARANG TAHUN 2015 - Aminah, Siti (Jurnal Geografi, 2016)
Analysis of the survey data and secondary data City Education Department Semarang School Enrollment AtCoastal Community District of Semarang Utara both GER and net enrollment ratio in 2015, in the Districtof Semarang north taken three village is Village Stage Lor the number of digits to a participatory Schoolselementary level 21.95 and 139.25 Junior level, Village Bandarharjo the number of elementary school aparticipatory Figures 70,71% and 18,12% Junior level, and Village Tanjung Mas by the number of digits toa participatory 105,59% elementary school and junior high school level of 59,38%. Direct role and the roleof parents indirectly in the northern district of semarang can be seen that the role of parents in childrenseducation in the District of North Semarang can dikriteriakan very high.